Generation of a high quality library of bioactive filamentous actinomycetes from extreme biomes using a culture-based bioprospecting strategy - Świecimska, Magdalena; Golińska, Patrycja; Goodfellow, Michael (Frontiers in Microbiology, 2023)
Introduction Filamentous actinomycetes, notably members of the genus Streptomyces, remain a rich source of new specialized metabolites, especially antibiotics. In addition, they are also a valuable source of anticancer and biocontrol agents, biofertilizers, enzymes, immunosuppressive drugs and other biologically active compounds. The new natural products needed for such purposes are now being sought from extreme habitats where harsh environmental conditions select for novel strains with distinctive features, notably an ability to produce specialized metabolites of biotechnological value. Methods A culture-based bioprospecting strategy was used to isolate and screen filamentous actinomycetes from three poorly studied extreme biomes. Actinomycetes representing different colony types growing on selective media inoculated with environmental suspensions prepared from high-altitude, hyper-arid Atacama Desert soils, a saline soil from India and from a Polish pine forest soil were assigned to taxonomically predictive groups based on characteristic pigments formed on oatmeal agar. One hundred and fifteen representatives of the colour-groups were identified based on 16S rRNA gene sequences to determine whether they belonged to validly named or to putatively novel species. The antimicrobial activity of these isolates was determined using a standard plate assay. They were also tested for their capacity to produce hydrolytic enzymes and compounds known to promote plant growth while representative strains from the pine forest sites were examined to determine their ability to inhibit the growth of fungal and oomycete plant pathogens. Results Comparative 16S rRNA gene sequencing analyses on isolates representing the colour-groups and their immediate phylogenetic neighbours showed that most belonged to either rare or novel species that belong to twelve genera. Representative isolates from the three extreme biomes showed different patterns of taxonomic diversity and characteristic bioactivity profiles. Many of the isolates produced bioactive compounds that inhibited the growth of one or more strains from a panel of nine wild strains in standard antimicrobial assays and are known to promote plant growth. Actinomycetes from the litter and mineral horizons of the pine forest, including acidotolerant and acidophilic strains belonging to the genera Actinacidiphila,Streptacidiphilus and Streptomyces, showed a remarkable ability to inhibit the growth of diverse fungal and oomycete plant pathogens. Discussion It can be concluded that selective isolation and characterization of dereplicated filamentous actinomyctes from several extreme biomes is a practical way of generating high quality actinomycete strain libraries for agricultural, industrial and medical biotechnology.